Advances in protein chemistry (Academic, 2003)
The content of this volume is designed to reach a wide audience, including those involved with relevant technologies such as electrophoresis and mass spectrometry, to those interested in how proteomics can benefit research. A wide range of techniques are discussed, each specifically designed to address different needs in proteomic analysis. The concluding chapter discusses the important issue related to handling large amounts of data accumulated in proteomic studies. It discusses proteomics in the postgenomic age. It includes various strategies for quantitative proteomics. It covers the role of MS in structural functional proteomics and proteomics in drug discovery and bioinformatics.